Episodes of Mental Health Treatment Among a Nationally Representative Sample of Children and Adolescents. (June 2014) - Saloner, Brendan; Carson, Nicholas; Cook, Benjamin Lê
Despite renewed national interest in mental health care reform, little is known about treatment patterns among youth in the general population. Using longitudinal data from the Medical Expenditure Panel Survey, we examined both initiation and continuity of mental health treatment among 2, 576 youth aged 5 to 17 with possible mental health treatment need (defined as a high score on a parent-assessed psychological impairment scale, fair/poor mental health status, or perceived need for counseling). Over a 2-year period, fewer than half of sampled youth initiated new mental health treatment. Minority, female, uninsured, and lower-income youth were significantly less likely to initiate care. Only one third of treatment episodes met criteria for minimal adequacy (≥4 provider visits with psychotropic medication treatment or ≥8 visits without medication). Episodes were significantly shorter for Latino youth. Efforts to strengthen mental health treatment for youth should be broadly focused, emphasizing not only screening and access but also treatment continuity.